USM VICE-CHANCELLOR CONGRATULATES THREE NEWLY APPOINTED ASM FELLOWS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 6 May 2016 Universiti Sains Malaysia (USM) ViceChancellor, Professor Dato’ Dr. Omar Osman congratulated three USM academicians who were recently appointed as new Fellows of the Academy of Sciences Malaysia (ASM).